Claude Lévi-Strauss’s Inspiration in Sociology: Baudrillard’s Theory of the Consumer Society - Maršálek, Jan (Teorie vědy / Theory of Science, 2009)
Contrary to what is often thought, the structuralist approach has never been adopted in French sociology very extensively. When speaking about structuralism in this discipline, the work of Pierre Bourdieu is generally referred to. The present paper is intentionally heading in another direction and is questioning Lévi-Straussian traces in Baudrillard’s theory of the consumer society. First, Baudrillard acknowledges being in debt to Lévi-Strauss for his conception of consumption as a language. In this perspective exchanged goods are understood as object-signs. We believe nevertheless that Baudrillard goes even further when he analyzes the phenomenon of absurd violence, bearing in mind – even he does not directly disclose it – Lévi-Strauss’ concept of “free signifier”. All the same we finally conclude that Baudrillard’s use of Lévi-Strauss is rather cursory. Despite this fact it is of interest: Thus we follow Baudrillard’s analysis and consider the problem of social criticism, which is one of the main topics of his writings here discussed.